Evaluation of IL-6 levels and +3954 polymorphism of IL-1β in burning mouth syndrome: A systematic review and meta-analysis - Campello, Camilla Porto (2020)
This study evaluated IL-6 salivary levels as well as the +3954 polymorphism of IL-1β in patients with burning mouth syndrome and healthy individuals, through case-control studies. This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We conducted this research in PubMed/MEDLINE, Cochrane Library and Web of Science databases. The risk of bias was measured based in the Newcastle-Ottawa Scale. Researches with a group of patients with burning mouth syndrome and a control group in which the presence of the +3954 polymorphism of IL-1β and/ or IL-6 salivary levels through non-stimulated saliva were evaluated to detect if this interleukin concentrations are increased in patients and if the polymorphism is a risk factor for this syndrome. We identified seven studies with total of 440 participants, 229 patients with burning mouth syndrome and 211 healthy controls, ages 24-84 years old. The female gender was predominant. Patients in the majority of studies did not present increased levels of IL-6 and the +3954 polymorphism of IL-1β is not a risk factor for this syndrome. A few studies researched biomarkers in this pathology and more investigations are required not only to identify salivary levels and the polymorphism evaluated, but also other interleukins and polymorphisms in order to clarify the etiopathogenesis of this syndrome as well as for propose new diagnostic methods and treatments.